2020
DOI: 10.1136/bmjopen-2020-037464
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence against healthcare professionals in a multiethnic area: a cross-sectional study in southwest China

Abstract: ObjectiveThe purpose of this study is to examine workplace violence (WPV) towards healthcare professionals in a multiethnic area in China, including prevalence, influencing factors, healthcare professionals’ response to WPV, expected antiviolence training measures and content, and evaluation of WPV interventions.DesignA cross-sectional study.SettingA grade III, class A hospital in the capital of Yunnan Province, which is the province with the most diverse ethnic minority groups in China.ParticipantsIn total, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
2
11
2
1
Order By: Relevance
“…In our study, female healthcare workers were more often assaulted compared with males, despite their professional category and this is in line with the current evidence worldwide [ 5 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, female healthcare workers were more often assaulted compared with males, despite their professional category and this is in line with the current evidence worldwide [ 5 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…31 In this study, men were found to be exposed to physical violence and verbal harassment more than a woman, which is consistent with some previous study results. 5,24,32,33 Unlike our results, WPV in an emergency was found to be similarly experienced by male and female physicians (79% vs 75%; P = .65, respectively). 32 The study found that doctors were more vulnerable to WPV, which is consistent with some previous research, 5,10,33 while some research did not support this result, 34,35 which may be because physicians are the front line of health care in the Turkish health care system.…”
Section: Discussioncontrasting
confidence: 98%
“…This study obtained a 43.3% prevalence of WPV among healthcare workers, of which 84.6% were non-physical, and the remaining 15.4% was physical. The prevalence is lower than a study conducted in China (49.2%) [17] but higher than in India (40.8%) [18]. A Turkish study of doctors identified a very high 78.1% prevalence of WPV in the emergency department [16].…”
Section: Discussionmentioning
confidence: 60%